2022
DOI: 10.1039/d1en01211h
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotubes improve nitrogen use efficiency and nutritional quality inBrassica campestris

Abstract: In order to explore the effects of addition of multi-walled carbon nanotubes (MWCNTs) to soil on the nutritional quality and nitrogen assimilation and utilization by Brassica campestris, a pot experiment...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…11,12 Among the various NMs studied, multi-walled carbon nanotubes (CNTs) and iron oxide nanoparticles (Fe 2 O 3 NPs) are considered as potential candidates for enhancing plant growth, defense systems, and metabolic acceleration with less toxicity. [13][14][15][16] For example, foliar applications of 3 mg L −1 Fe 2 O 3 NPs enhanced the antioxidant enzyme activity as well as anthocyanins and flavonoids levels in Hibiscus sabdariffa plants. 14 In addition, an approximately 4-fold increase in rosmarinic acid (RA) in the leaves of Salvia verticillata plants sprayed with 50 mg L −1 CNTs was observed compared to the control, which may have been due to the enhanced RA synthase activity and gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Among the various NMs studied, multi-walled carbon nanotubes (CNTs) and iron oxide nanoparticles (Fe 2 O 3 NPs) are considered as potential candidates for enhancing plant growth, defense systems, and metabolic acceleration with less toxicity. [13][14][15][16] For example, foliar applications of 3 mg L −1 Fe 2 O 3 NPs enhanced the antioxidant enzyme activity as well as anthocyanins and flavonoids levels in Hibiscus sabdariffa plants. 14 In addition, an approximately 4-fold increase in rosmarinic acid (RA) in the leaves of Salvia verticillata plants sprayed with 50 mg L −1 CNTs was observed compared to the control, which may have been due to the enhanced RA synthase activity and gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports revealed that the improvement of N availability of plants offered an effective strategy to simultaneously improve N use efficiency (NUE) and grain yield. Herein, the soil application of CDs significantly increased N content in the shoots and roots of soybeans by 18.5% and 14.8%, respectively (Figure e), while the N content in the soil decreased by 7.5% (Figure f). It can be seen that the N utilization efficiencies in soybean shoots and roots were increased by 18.5% and 14.8%, respectively (Figure S6a).…”
Section: Resultsmentioning
confidence: 78%
“…Moreover, it may be feasible to combine conventional and nanofertilizers as a co-dosing approach to increase yield even further (Fig. 2), which is currently widely explored, for example, co-dosing fertilizer with carbon-based nanomaterials [32][33][34] . The benefit of the co-dosing method is that it lowers the total cost of fertilizer application (through the use of conventional fertilizers) while increasing the yield (through the use of the nanofertilizers).…”
Section: Cost-benefit Analysis Of Nanofertilizersmentioning
confidence: 99%
“…in which X R is the recommended dosage for maize (180 kg N ha −1 ). In terms of the environmental cost of nanofertilizers, it is assumed that nitrate leaching, ammonia volatilization and the release of NO and N 2 O can be reduced by 50%, 10% and 20%, respectively, on the basis of previous findings about NUE improvement strategies 33,34,42,62,65,66 . Notably, nitrate leaching, ammonia volatilization and the release of gaseous NO and N 2 O are closely related to NUE 66 .…”
Section: Articlementioning
confidence: 99%